2008
DOI: 10.1016/j.pupt.2008.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Roflumilast attenuates pulmonary inflammation upon segmental endotoxin challenge in healthy subjects: A randomized placebo-controlled trial

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting galley proof before it is published in its final citable form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. Objectives: The aim of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 24 publications
3
47
0
Order By: Relevance
“…A novel human airway inflammation study limiting LPS challenge to the airways used segmental endotoxin challenge in healthy subjects during bronchoscopy [27]. This model gives limited systemic but only local inflammatory responses and is invasive to the subjects.…”
Section: Discussionmentioning
confidence: 99%
“…A novel human airway inflammation study limiting LPS challenge to the airways used segmental endotoxin challenge in healthy subjects during bronchoscopy [27]. This model gives limited systemic but only local inflammatory responses and is invasive to the subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality due to COPD was similar in both treatment-arms in both studies The mechanism of the improvements in lung function, exacerbation rates and quality of life scores cannot be attributed to a direct bronchodilating action of this drug class, as we have previously discussed for cilomilast. It is more likely that these beneficial actions are secondary to an anti-inflammatory activity of roflumilast, although the reduction in pro-inflammatory cell numbers found in two other studies was modest, reflecting a 30-50% suppression of inflammatory cell numbers [43,44] and reduced the number of airway CD8+ T lymphocytes and CD68+ macrophages by approximately 40-50% [30]. Other evidence of an anti-inflammatory mechanism stems from in vitro studies which reported that cilomilast reduced the level of TNF-alpha (25% decrease), GMCSF (46% decrease) and neutrophil chemotactic factors (35% decrease) with no effect on IL-8 released by epithelial cells from COPD patients [45].…”
Section: Roflumilast: Pharmacokinetics Clinical Efficacy From Phase mentioning
confidence: 96%
“…[14][15][16][17][18] A breakthrough of PDE4 inhibitors as anti-inflammatory agents came up with second generation Roflumilast (3) Dexas ® by Merck Sharp & Dohme, a selective, long-acting inhibitor of the enzyme PDE4B. [19][20][21][22] Continuous efforts in this era lead to the discovery of Cilomilast (4) Ariflo ® , the most advanced PDE4 inhibitor developed by GSK. 10) Many quinoline based PDE4B inhibitors were also reported in literature among which SCH 351591(5) and SCH 365351 (6).…”
Section: )mentioning
confidence: 99%